The immunology of organ transplantation. Issue 7 (July 2020) - Phillips, Benedict L.; Callaghan, Chris
Abstract: Transplantation is the gold standard treatment for many patients with end-stage organ failure. In addition to the medical and surgical challenges in organ transplantation, the major biological barrier is immunological. This barrier may lead to graft rejection and loss. An understanding of transplant immunology is essential in order to care for transplant recipients. The aims of this article are to describe commonly used immunological terms, the immunology of graft rejection, the different types of rejection and how this process may be prevented with immunosuppressive therapy. Finally, the article will review the practical translations of transplant immunology. This article aims to afford the reader an overall view of basic transplant immunology that will be of use in the clinical setting or in preparation for examinations.